PROTOCOL FOR PERIODONTAL TOOTH PREPARATION WITH ER-YAG LASER BEFORE FIXED PROSTHETIC TREATMENT - Plamen Nenkov; Metodi Z. Abadzhiev; Polina Velcheva (Peytchinski Publishing, 2020)
Purpose: Every clinician encounter isses with problematic periodontal tissue around teeth intended to be treatet prosthetically. Swollen, reddish, with deeper periodontal pockets and and impossible to dry up with air flow. Such teeth should be treated rapidly and minimally invasive. The purpose of this study was to create an algorithm for periodontal tooth preparation with Er-YAG laser before prosthetic treatment. Material/Methods: It was used examination and diagnosis of teeth for the purpose of prosthodontic treatment according to the periodontal status by using UNC 15 perio-probe and electronic periodontal probe Pa-On and Er-YAG dental laser. There were examined 216 periodontal units, 106 of them treated according to the suggested protocol. An innovative approach was used by considering all treated teeth suitable for impression by the visual indicator -periodontal margin condition (lack of inflammatory symptoms, lack of bleeding, lack of redness, presence of pink, dense gingiva. Record of the day with "pink gingiva" appear was made. Results: 216 units measured with a conventional and electronic periodontal probe in inflammatory status and after periodontal treatment. It was registered a significant difference between the data from the conventional periodontal probe and the electronic one. Teeth prepared for prosthetic treatment were 106. By using a blind randomized clinical trial, 50% of them were prepared for prosthetic impression by using ultrasonic and the other half by using Er-YAG laser. Teeth prepared for Prosthodontic impression are heathy between 2nd and 7th day after preparation (61.54% -2nd day; 38.46% - 7th day) while the controlled group is between the 14th and the 21st day (33.33% -14th day; 62.96% - 21st day). The total amount of attachment gain in such a short period of time by the protocol suggested by the authors is 1mm. Conclusions: Considerable dental units show difference in periodontal pocket depth measurement to such degree that could lead to misdiagnosis and unnecessary treatment. Great difference is observed mainly between gingival pocket depth and superficial periodontitis.